Konstruksi Teologi Revolusioner Hassan Hanafi - Lukman Hakim (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2010)
Historically, Islamic theology ever became a soul of revolution thatalleviated the Islamic empires to the most glorious civilization on the world. By the rationalized theological system, Islam succeededin enlightening human thoughts. Ironically, the glory could not bemaintained by past Muslim which caused the civilization wentunder and could not be able to compete with other raisingcivilizations. Theologically, the collapse of muslim civilization wascaused by Muslim inability to cultivate the revolution spirit thatlies within Islamic theological doctrines. The presence of HassanHanafi becomes a fresh air that blows the development of Islamiccivilization by offering the concept of revolutionary theology. Hassan Hanafi’s construction of revolutionary theology focuses onfour big steps covering (1) revitalization of the enrichment ofclassical Islam (Ihya al-turats al qidim), (2) responding the westernchallenges (tahadda al hadarah al gha